2019
DOI: 10.1007/jhep03(2019)034
|View full text |Cite
|
Sign up to set email alerts
|

Leptogenesis from low energy CP violation

Abstract: We revisit the possibility of producing the observed baryon asymmetry of the Universe via thermal leptogenesis, where CP violation comes exclusively from the low-energy phases of the neutrino mixing matrix. We demonstrate the viability of thermal flavoured leptogenesis across seven orders of magnitude 10 6 < T (GeV) < 10 13 , using modern numerical machinery, where the lower bound can be reached only if flavour effects are taken into account and its value depends on the allowed degree of cancellation between t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 111 publications
3
74
0
Order By: Relevance
“…(57) and (58) Finally, we conclude this section by pointing out that our scenario also manages to account for the generation of the baryon asymmetry even if the CP -violating phases δ and σ in the PMNS matrix are the only source of CP violation during leptogenesis. This observation allows us to conclude that our scenario is compatible with the concept of leptogenesis from low-energy CP violation [80,[117][118][119][120][121][122][123][124][125][126]. To show that this is the case all we have to do is to fix the CIP parameter z I at z I = 0 in our numerical analysis.…”
Section: Overall We Find Very Good Agreement Between the Results In supporting
confidence: 59%
“…(57) and (58) Finally, we conclude this section by pointing out that our scenario also manages to account for the generation of the baryon asymmetry even if the CP -violating phases δ and σ in the PMNS matrix are the only source of CP violation during leptogenesis. This observation allows us to conclude that our scenario is compatible with the concept of leptogenesis from low-energy CP violation [80,[117][118][119][120][121][122][123][124][125][126]. To show that this is the case all we have to do is to fix the CIP parameter z I at z I = 0 in our numerical analysis.…”
Section: Overall We Find Very Good Agreement Between the Results In supporting
confidence: 59%
“…In this section we consider the possibility that the low energy CP phases (δ, α 21 and α 31 ) provide all of the CP violation necessary for leptogenesis to produce the observed BAU. In past work it has been shown that these phases are sufficient sources of CP violation in a mass range 10 6 < M (GeV) < 10 13 [25,[67][68][69][70][71][72][73][74] (for a review see, e.g., [75]), where there must be some fine-tuning for heavy Majorana neutrino masses M 10 9 GeV, if they are mildly hierarchical. Here we ask: Is it possible for purely the low energy phases to provide CP violation for successful leptogenesis within the Neutrino Option?…”
Section: Leptogenesis From Purely Low Energy Cp Violation In the Neutmentioning
confidence: 99%
“…See, for example, Refs. [18,19,20]. It is then discussed whether two right-handed neutrinos whose masses are TeV-scale can produce a sufficient amount of the BAU or not.…”
Section: Tev-scale Right-handed Neutrinosmentioning
confidence: 99%